The effect of entrepreneurial orientation, innovation capability and knowledge creation on firm performance: a perspective on small scale entrepreneurs - Nor Asiah Omar; Hasnan Md Aris; Muhamad Azrin Nazri (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this study is to examine the predictive effects of entrepreneurial orientation, innovation capability and knowledge creation on firm performance. Data for the study was collected using a cross-sectional quantitative survey. A total of 188 useable responses were collected from SMEs in Malaysia. The findings show that entrepreneurial orientation, innovation capability and knowledge creation have a positive impact on firm performance. Furthermore, the impacts of entrepreneurial orientation and innovation capability on knowledge creation are also examined in this study. The findings suggest that innovation capability is positively related to knowledge creation, but entrepreneurial orientation does not have a significant impact on knowledge creation. This study makes a considerable contribution to the existing literature on entrepreneurial orientation, innovation capability and knowledge creation of SMEs, particularly in regards to explaining the performance of Malaysian SMEs.